Acute alcohol intoxication impairs top-down regulation of stroop incongruity as revealed by blood oxygen level-dependent functional magnetic resonance imaging - Marinkovic, Ksenija; Rickenbacher, Elizabeth; Azma, Sheeva; Artsy, Elinor (Human brain mapping, 2012)
Functional neuroanatomy of executive functions has been delineated in a large number of neuroimaging studies using conflict‐inducing tasks. The neural basis of alcohol's effects on cognitive control is poorly understood despite the evidence of impaired ability to evaluate competing demands and to inhibit maladaptive responses. To investigate the effects of moderate intoxication, healthy social drinkers participated in both alcohol (0.60 g/kg ethanol for men, 0.55 g/kg for women) and placebo conditions while being scanned using blood oxygen level‐dependent (BOLD) functional magnetic resonance imaging (fMRI). A modified four‐color Stroop task combined reading and color naming and used manual responses. Twenty subjects (10 women) were instructed to press a button corresponding to the font color except when a word was written in gray in which case they had to respond to the meaning of the word. Alcohol increased reaction times and a tendency to make more errors on incongruent trials. Behavioral indices of alcohol‐induced premature responding correlated with the current drinking levels and impulsivity traits, suggesting an interaction between alcohol effects and personality predispositions. A distributed frontoparietal cortical network was activated by incongruity. However, moderate alcohol inebriation selectively attenuated anterior cingulate cortex (ACC) activation during both high‐conflict trials and erroneous responses, indicating vulnerability of the regulative function subserved by the ACC. By disrupting top–down, strategic processing, alcohol may interfere with goal‐directed behavior, resulting in poor self control. The present results support models proposing that alcohol‐induced prefrontal impairments diminish inhibitory control and are modulated by dispositional risk factors and levels of alcohol consumption. Hum Brain Mapp, 2012. © 2011 Wiley Periodicals, Inc.